2015
DOI: 10.1177/0956797615586402
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent Times, Rocky Relationships

Abstract: What influences how people feel about and behave toward their romantic partners? Extending beyond features of the partners, relationship experiences, and social context, the current research examines whether benign, relationship-irrelevant factors-such as one's somatic experiences-can influence relationship perceptions and interpersonal behavior. Drawing on the embodiment literature, we propose that experiencing physical instability can undermine perceptions of relationship stability. Participants who experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…L. Murray, Seery, et al, 2021). People also misattribute positive reminders of connection, confusing one source of security for another (Chen et al, 2015; Fay & Maner, 2012; Forest et al, 2015; Williams & Bargh, 2008). In fact, over time, repeatedly conditioning people to associate their romantic partner with highly desirable words and images even reduced the general sense of social isolation and disconnection underlying suicidal ideation (McNulty et al, 2019).…”
Section: Romantic Relationships: Satiating the Fundamental Goal To Fe...mentioning
confidence: 99%
See 1 more Smart Citation
“…L. Murray, Seery, et al, 2021). People also misattribute positive reminders of connection, confusing one source of security for another (Chen et al, 2015; Fay & Maner, 2012; Forest et al, 2015; Williams & Bargh, 2008). In fact, over time, repeatedly conditioning people to associate their romantic partner with highly desirable words and images even reduced the general sense of social isolation and disconnection underlying suicidal ideation (McNulty et al, 2019).…”
Section: Romantic Relationships: Satiating the Fundamental Goal To Fe...mentioning
confidence: 99%
“…The risk-regulation system functions to ensure that people surround themselves with intimates who are not going to reject or exclude them. It fulfills this function by linking the experience of social pain to defensive inclinations to devalue and withdraw from romantic partners, friends, and family members when they behave rejectingly (Forest et al, 2015;Kane et al, 2012; S. L. ; S. L. ; S. L. Murray & Holmes, 2009. For example, priming a rejecting significant other automatically activates thoughts of distancing oneself from that person, which blunts the pain of their rejection (Gillath et al, 2006;S.…”
mentioning
confidence: 99%
“…Participants in the unstable condition judged interpersonal relationships in general to be less stable than participants seated on stable chairs. They also expressed a greater desire for stability in any future partner than those in the already stably situated group (Forest et al, 2015). In a further study, students who reported being in a committed relationship for more than a year were randomly put into conditions of either physical instability (seated at a desk on a wobbly chair, composing a letter standing on one leg, or sitting on an inflatable cushion) or physical stability (solid chair, standing on both feet, firm cushion).…”
Section: Part 1: Bodily Activity Impacts Cognitive and Emotional Procmentioning
confidence: 99%
“…With the relationship found between a physical experience such as temperature, and an abstract concept such as a participant's need for romantic connection, it becomes plausible that other physical experiences could also impact a participant's inter est in romantic connection. Forest, Kille, Wood, and Stehouwer (2015) addressed this idea by placing participants in either a physically unstable (wobbly desk) or physically stable (standard desk) condition, and asked them to answer a series of relational ques tions measuring their interest in a potential partner. Participants in the physical instability condition were found to be less interested in the presented profile (because their cognitive processing felt more unstable) than participants in the physical stability condition, continuing to draw attention to the connection between experiencing physical stimuli and cognitive processes.…”
Section: Embodied Cognition and Relational Interestmentioning
confidence: 99%